α-Alkylation of N–C Axially Chiral Quinazolinone Derivatives Bearing Various ortho-Substituted Phenyl Groups: Relation between Diastereoselectivity and the ortho-Substituent - Matsuoka, Mizuki; Iida, Asumi; Kitagawa, Osamu (Synlett, 2018)
2-Ethylquinazolin-4-one derivatives bearing various ortho-substituted phenyl groups were revealed to possess a stable C–N axially chiral structure at ambient temperature. The reactions of alkyl halides with the anionic species prepared from these quinazolinones were systematically explored. The α-alkylation reactions proceeded with diastereoselectivities ranging from 1:1 to >50:1, depending upon the steric bulk of the ortho-substituent, to afford products having the elements of axial and central chirality in high yields (85–98%).
Keywords: axial chirality; quinazolinones; alkylation; diastereoselectivity